The Looming Cancer: A Qualitative Study on the Experience of Living with Chronic Lymphocytic Leukemia (CLL) before the Initiation of Treatment - Kyrou, Dimitrios; Stavrogianni, Konstantina; Koulierakis, George; Vrontaras, Nikolaos; Stamatopoulos, Kostas; Karamanidou, Christina (European Journal of Cancer Care, 2024)
Purpose. This study aimed to study the challenges and ways of coping with living with chronic lymphocytic leukemia (CLL) before the initiation of treatment. Methods. Semistructured interviews were carried out with 8 people living with CLL (4 males and 4 females) who had never received any treatment. Interpretative phenomenological analysis was utilized for the analysis of the data. Results. The following three themes were developed: (1) “Still waters run deep” highlights the contrast between living with minimal symptoms while experiencing high anxiety for the future, (2) “Surviving uncertainty” portrays participants’ supportive networks, communication challenges, and internal coping mechanisms to face the threatening overtones of CLL, and (3) “Turning over a new leaf” delineates participants’ realization of life’s finiteness and the way this acts as a nudge for psychological growth. Conclusion. Despite the limited physical discomfort, the CLL diagnosis and the watch-and-wait phase bring about psychological distress, which drives meaning-making efforts and an array of coping mechanisms, potentially leading to posttraumatic growth processes for people living with CLL.